Dual THz Wave and X-ray Generation from a Water Film under Femtosecond Laser Excitation - Hsin-hui Huang (Nanomaterials, 2018)
Simultaneous emission of the THz wave and hard X-ray from thin water free-flow was induced by the irradiation of tightly-focused femtosecond laser pulses (35 fs, 800 nm, 500 Hz) in air. Intensity measurements of the THz wave and X-ray were carried out at the same time with time-domain spectroscopy (TDS) based on electro-optic sampling with a ZnTe(110) crystal and a Geiger counter, respectively. Intensity profiles of the THz wave and X-ray emission as a function of the solution flow position along the incident laser axis at the laser focus show that the profile width of the THz wave is broader than that of the X-ray. Furthermore, the profiles of the THz wave measured in reflection and transmission directions show different features and indicate that THz wave emission is, under single-pulse excitation, induced mainly in laser-induced plasma on the water flow surface. Under double-pulse excitation with a time separation of 4.6 ns, 5–10 times enhancements of THz wave emission were observed. Such dual light sources can be used to characterise materials, as well as to reveal the sequence of material modifications under intense laser pulses.